Volatile Organic Compounds in Human Breath - Monika Karunagaran; Pratibha Ramani; S Gheena; R Abilasha; R Hannah (Wolters Kluwer Medknow Publications, 2022)
A comprehensive analysis of volatile organic compounds (VOCs) from the exhaled breath sample is termed as breathomics. Breath samples are a complex mixture composed of a multitude of VOCs and other molecules. The analysis of total VOCs in exhaled breath provides a promising tool for the diagnosis of many diseases because it enables the observation of biochemical processes in the body in a non-invasive way. VOCs are produced in various physiological and pathophysiological conditions thus making it a potential biomarker for several diseases.